Missing voices: Aboriginal experiences in the Great War. Issue 2 (3rd April 2017) - Maynard, John
Abstract: Aboriginal involvement in World War I is at once complex and full of contradictions. During the Great War, many Aboriginal people and communities were keen to enlist and supportive of the war effort while others spoke out against conscription and the war. It is important to trace Aboriginal voices both during and after the war to comprehend what Aboriginal people had to say about the conflict. This article seeks to provide answers to some of these tantalising issues, and snapshots of the Aboriginal WWI experience. These complex stories will fill gaps in the mythic Australian First World War narrative.